ANALISIS PEMANFAATAN AIR BUANGAN PLTA MUSI UNTUK MEMENUHI KEBUTUHAN AIR IRIGASI KABUPATEN KEPAHIANG DAN BENGKULU TENGAH - Rezky Haredho Akbar; Khairul Amri; Yuzuar Afrizal (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
Bengkulu province is an area with high population growth, and it affects water demand, including rice field irrigation water. In a certain period, there was a drought on farming irrigation water in Bengkulu. The Water supply has to be maintained to fullfill the irrigation water demand. Musi Hydroelectric outlet water is one source to fulfill irrigation water demand. it is located at Ujan Mas, Kepahiang regency where the hydroelectric outlet water reaches billions of cubic in a year. Thus, there is potential to optimize rice-field irrigation water demand. The analysis method used in this study is a comparison between fount water supply and rice-field irrigation water demand based on Irrigation Planning Criteria (KP-01) in 1986. The result of the study is monthly water balance charts which illustrate the comparison between the water amount on hydroelectric outlet (PLTA) and irrigation water demand in Kepahiang and Bengkulu Tengah regency. The result of the study shows that outlet water of Musi hydroelectric (PLTA) can fulfill the irrigation water demand in Kepahiang and Bengkulu Tengah regency.